2012
DOI: 10.1128/aac.01209-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Hepatitis C Virus Replication of Combinations of Direct-Acting Antivirals, Including NS5A Inhibitor Daclatasvir

Abstract: Three hepatitis C virus (HCV) inhibitors, asunaprevir (ASV; BMS-650032), daclatasvir (DCV; BMS-790052), and BMS-791325, each targeting a different nonstructural protein of the virus (NS3, NS5A, and NS5B, respectively), have independently demonstrated encouraging preclinical profiles and are currently undergoing clinical evaluation. Since drug-resistant variants have rapidly developed in response to monotherapy with almost all direct-acting antiviral agents (DAAs) for HCV, the need for combination therapies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 60 publications
5
46
0
Order By: Relevance
“…In addition, several DAAs, including inhibitors for NS3/4A protease, NS5A, and NS5B polymerase, are currently in clinical trials. Several reports have shown that in vitro replication of HCV RNA is significantly inhibited by treatment with daclatasvir (NS5A inhibitor) and asunaprevir (NS3 protease inhibitor), and these two DAAs are also effective for patients infected with genotype 1 HCV who showed no response to previous therapy with peg-IFN-␣ and RBV (6)(7)(8). On the other hand, it has been shown that drug-resistant breakthrough viruses emerge during treatment with DAAs (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In addition, several DAAs, including inhibitors for NS3/4A protease, NS5A, and NS5B polymerase, are currently in clinical trials. Several reports have shown that in vitro replication of HCV RNA is significantly inhibited by treatment with daclatasvir (NS5A inhibitor) and asunaprevir (NS3 protease inhibitor), and these two DAAs are also effective for patients infected with genotype 1 HCV who showed no response to previous therapy with peg-IFN-␣ and RBV (6)(7)(8). On the other hand, it has been shown that drug-resistant breakthrough viruses emerge during treatment with DAAs (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Until recently, there were no effective prophylactic or therapeutic vaccines available for the treatment of HCV infections. The current antiviral therapy against HCV consists of pegylated IFNa and ribavirin, together with directly acting antivirals (DAAs) such as the protease inhibitors telaprevir, boceprevir and simeprevir, and the nucleotide analogue sofosbuvir (Cox, 2015;Kohli et al, 2014;Pelosi et al, 2012). However, the use of currently available DAAs is limited because of a series of problems including safety profiles, virus breakthroughs and comparatively higher medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a phase III study demonstrated that a 24-week combined regimen of daclatasvir (DCV) and asunaprevir (ASV) was highly effective in patients with HCV genotype 1b infections [10]. DCV was the first nonstructural protein 5A (NS5A) replication complex inhibitor to show potential efficacy against all HCV genotypes [11][12][13][14]. ASV is a second-generation NS3 (nonstructural protein 3) protease inhibitor that exhibited strong antiviral activity against HCV genotypes 1 and 4.…”
Section: Introductionmentioning
confidence: 99%